Blood culture use in the emergency department in patients hospitalized with respiratory symptoms due to a nonpneumonia illness. Issue 8 (22nd April 2014) - Makam, Anil N.; Auerbach, Andrew D.; Steinman, Michael A.
<x xml:space="preserve">Abstract</x> BACKGROUND Guidelines and performance measures recommend obtaining blood cultures in selected patients hospitalized with community‐acquired pneumonia (CAP). Due to inherent diagnostic uncertainty, there may be spillover effects of these recommendations on other conditions that resemble pneumonia. METHODS Using data from the 2002 to 2010 National Hospital Ambulatory Medical Care Survey, a nationally representative sample of emergency department (ED) visits in the United States, we analyzed trends in obtaining cultures in patients hospitalized with respiratory symptoms due to a nonpneumonia illness using linear regression. RESULTS The most common primary admission diagnoses for these visits included heart failure (16%), chronic obstructive pulmonary disease (13%), and chest pain (12%). The proportion of cultures collected in the ED during these visits increased from 10% (95% confidence interval [CI]: 7%‐14%) in 2002 to 20% (95% CI: 16%‐26%) in 2010 (P < 0.001 for the trend). This represented a parallel increase compared to patients hospitalized with CAP (P = 0.12 for the difference in trends). CONCLUSIONS The increase in collecting cultures in the ED in patients hospitalized with respiratory symptoms due to a nonpneumonia illness suggests an important potential unintended consequence of blood culture recommendations for CAP. More attention to the judicious use of blood cultures to reduce harm and costs is needed. Journal of Hospital Medicine 2014;9:521–524. © 2014 Society of Hospital Medicine